The Abbott PanBio WHO emergency use listed, rapid, antigen-detecting point-of-care diagnostic test for SARS-CoV-2: evaluation of the accuracy and ease-of-use [research data] - Krüger, Lisa; Gaeddert, Mary; Tobian, Frank; Lainati, Federica; Gottschalk, Claudius; Klein, Julian; Schnitzler, Paul; Kräusslich, Hans-Georg; Nikolai, Olga; Lindner, Andreas; Mockenhaupt, Frank Peter; Seybold, Joachim; et al. (Universität, 2021)
This repository includes data from a prospective, multi-centre diagnostic accuracy study. The study was conducted at two sites in Germany, Heidelbe...
Grant information: Forschung und Kunst Baden-Württemberg (MWK), Foundation for Innovative New Diagnostics (FIND), University Hospital Heidelberg, Charité - Universitätsmedizin Berlin
Gesehen am 30.04.2021
Keywords: Forschungsdaten; Datenbank